SULUP MARRIAGE AND LEGAL PLURALISM: NEGOTIATING CUSTOMARY, ISLAMIC, AND STATE LAW IN TIDORE SOCIETY - Abu Sahman Nasim; Syaifuddin Syaifuddin; Marwa Marwa; Rifda Nasir; Muhammad Ufuqul Mubin; Abu Sanmas (Universitas Nurul Jadid, 2026)
This study examines the socio-legal construction of the Sulawesi marriage tradition as a traditional marriage practice in the community of Gamtufkange Village, Tidore Islands City, as well as its interaction with Islamic law and state law. Nikah sulup is a procession of marriage contracts that is carried out behind closed doors before the implementation of the official contract in front of the headman, which is based on a certain time calculation by the traditional elders by looking at the positions of the moon and stars. This study uses a qualitative method with a sociology of law and 'urf approaches, through observation, interviews, and documentation. The results of the study show that sulup marriage is seen as a form of cultural effort to avoid things that are considered bad in domestic life, as well as provide psychological calm for couples. From a socio-legal perspective, this practice reflects the existence of legal pluralism, where customary norms coexist and negotiate with sharia norms and state law. Normatively, sulup marriage has not met the formal legal requirements of the state so that an official re-contract is still carried out. However, in the perspective of 'urf, this tradition can be categorized as 'urf sahih as long as it does not contradict the basic principles of sharia. This research confirms that law is not only understood as a normative text, but also as a social practice that lives in society.